Quantifying consumer taste in trade: Evidence from the food industry - Bee-yan Aw; Yi Lee; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2023)
This paper develops an empirical model of consumer taste in twenty-nine Belgium food industries for the period from 1998-2005 to generate a "taste distance" measure of over 1,800 firm-product exports to 53 country destinations. We estimate consumer taste using a control function approach and perform a decomposition of export revenues of firm-products to establish the importance of representative consumer taste relative to quality and marginal cost in export success. We find substantial taste heterogeneity in food exports across destination countries. Overall, in the large majority of food exports, consumer taste is an important and separate demand determinant to explain export revenues. Depending on the product, taste for a product explains between 4-30% of export revenues. Thus, any taste shock due to events such as pandemics or climate change, may induce substantial changes in export profitability of firms.
Keywords: F12; F14; 330; consumer taste; quality; productivity; exports; firm-product; food